Soil water storage and water balance of spring barley crops on the erosion-hazardous slope - Ivan V. Batishchev; Isida N. Ilyinskaya (Мелиорация и гидротехника, 2023)
Purpose: to determine the influence of soil cultivation methods on the value of soil water storage, water balance and water consumption deficit of spring barley on an erosion-hazardous slope on ordinary chernozems. Materials and methods. During the research, the methodological approaches by S. A. Vorobyev, A. N. Kostyakov, S. I. Kharchenko, A. N. Postnikov were used. The experimental design provides for three options of soil cultivation: moldboard plowing, non-moldboard (chiseling) and combined (slotted) plowing. Results. As a result of the research, the advantage of chisel primary cultivation was revealed in terms of moisture reserves accumulation in snow: in the fall-plow it allowed accumulating on average 16.6 % more water than with moldboard tillage. Research has shown that the main flow component of water balance is the total water consumption of spring barley, which varied during the growing season depending on the phase of crop growth and development and on the method of soil cultivation; differences in the productive moisture reserves with the advantage of non-moldboard methods of soil cultivation were noted. The greatest differences were observed on the date of barley sowing; at this time, the excess in water storage in the meter layer was 9.9 % with combined tillage and it was 10.6 % with chiseling, relative to the same indicator with moldboard treatment. Conclusions. It was found that the intensity of the decrease in water storage rose, starting from the earing phase, especially during moldboard cultivation. In the longest period from sowing to booting (97–110 days), an average of approximately 50 % of the total moisture is consumed, from the booting phase to the earing and from the earing phase to milky-wax ripeness by 20 %, and in the last period from milky-wax ripeness to the complete ripeness of corn is only 10 % moisture. In general, during the growing season, non-moldboard cultivation allowed reducing the water consumption deficit of spring barley to 4.7–5.4 % compared to the control, which is very significant under the conditions of a moisture deficit amounting to 276 mm during this period.